IMPROVING LEARNING MOTIVATION BY APPLYING USER-CENTRED DESIGN AND AUGMENTED REALITY ON 3D INTERACTIVE APPLICATION - Ramadhani, Shumaya Resty; Limin, Fiona Stefani (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2023)
Conventional methods in teaching are still prevalent in the educational field to present knowledge to students. This method is still relevant today; however, it needs technology to enhance the experience and support an intelligent education system. Witama Primary School is one of the schools that applies modern technologies in teaching processes to improve learning motivation, especially in natural science. Students need an interactive instrument or tool that attracts attention and boosts their learning motivation while studying solar systems using a smartphone. Therefore, to present a virtual solar system experience, this study aims to create an interactive 3D solar system using Augmented Reality (AR) on iOS mobile-based by implementing a user-centered design (UCD) method to understand requirements and expectations. UCD consists of four main stages, specifying the context of use, user and organizational requirements, product design solution, and evaluation design before developing the system to ensure the finery development process as the goal is to improve the student’s focus and learning motivation. According to the User Experience Questionnaire results to thirty respondents, the obtained aspect of attractiveness is 2.222, the perspicuity aspect is 2.129, the efficiency aspect is 1.902, the dependability aspect is 1.689, the stimulation aspect is 2.222, and the novelty aspect is 1.727. Overall results showed that the interactive mobile app is in the good to excellent range. Moreover, the students and teachers find the product exciting and feel motivated to use the mobile app further